2000
DOI: 10.1016/s0006-3495(00)76681-1
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Currents in Hair Cells Isolated from Semicircular Canals of the Frog

Abstract: L-type and R-type Ca(2+) currents were detected in frog semicircular canal hair cells. The former was noninactivating and nifedipine-sensitive (5 microM); the latter, partially inactivated, was resistant to omega-conotoxin GVIA (5 microM), omega-conotoxin MVIIC (5 microM), and omega-agatoxin IVA (0.4 microM), but was sensitive to mibefradil (10 microM). Both currents were sensitive to Ni(2+) and Cd(2+) (>10 microM). In some cells the L-type current amplitude increased almost twofold upon repetitive stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
86
1

Year Published

2003
2003
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 42 publications
8
86
1
Order By: Relevance
“…Figure 1 shows examples of Ca 2ϩ current traces generated from hair cells. In agreement with earlier studies (Hudspeth and Lewis 1988;Martini et al 2000;Smotherman and Narins 1999;Zidanic and Fuchs 1995), the DHP-sensitive Ca 2ϩ current in hair cells has a rapid onset and inactivates slowly. Despite the fact that the channel has been identified as Ca V 1.3␣ 1 channel (Kollmar et al 1997a), the current profile of the expressed-channel in HEK 293 cells is in sharp contrast to that in hair cells.…”
Section: R E S U L T Ssupporting
confidence: 92%
“…Figure 1 shows examples of Ca 2ϩ current traces generated from hair cells. In agreement with earlier studies (Hudspeth and Lewis 1988;Martini et al 2000;Smotherman and Narins 1999;Zidanic and Fuchs 1995), the DHP-sensitive Ca 2ϩ current in hair cells has a rapid onset and inactivates slowly. Despite the fact that the channel has been identified as Ca V 1.3␣ 1 channel (Kollmar et al 1997a), the current profile of the expressed-channel in HEK 293 cells is in sharp contrast to that in hair cells.…”
Section: R E S U L T Ssupporting
confidence: 92%
“…Finally, neurotransmitter release by hair cells onto afferent nerve terminals of the vestibular nerve is mediated by Ca 2+ entry via presynaptic VGCCs. Although the nimodipine-sensitive Ca 2+ current contributes substantially to the VGCC in vestibular hair cells (Hudspeth and Lewis 1988;Prigioni et al 1992;Martini et al 2000;Rispoli et al 2001), our behavioral and electrophysiological analyses of the vestibular system of the a 1D )/) mice show that in addition, there is a non-nimodipine-sensitive current. In contrast to the auditory system, the vestibular hair cells employ multiple VGCCs that mediate neurotransmitter release to ensure proper balance.…”
Section: Discussion a 1dmentioning
confidence: 58%
“…ever, recent reports have demonstrated that hair cells in lower vertebrates and mammals do express nimodipine-insensitive Ca 2+ currents (Su et al 1995;Martini et al 2000;Platzer et al 2000;RodriguezContreras and Yamoah 2001). Although the functions of the non-L-type current remain unclear, their voltage-dependent properties suggest a possible function in tonic release of neurotransmitters (Martini et al 2000;Rodriguez-Contreras and Yamoah 2001).…”
Section: Discussion a 1dmentioning
confidence: 99%
See 2 more Smart Citations